(untitled) (Journal of the College of Basic Education, 2022)
The current research is concerned with the study of expression in the sculptural achievement of Jamal Al-Sigini and Sami Muhammad in a comparative study between them to show the expressive, formal and aesthetic characteristics of the three-dimensional sculptures of both sculptors. Thus, the research problem in the first chapter was linked to a basic issue, which is that most of the artistic or aesthetic studies did not address the topic of the research. The characteristic of expression in the sculptural achievement of Arab sculptors was the following question: What is the nature of expression by these two sculptors and what are the aspects of comparison between them in this field?